Episodic Memory as a Propositional Attitude: A Critical Perspective - Sant'Anna, André (Frontiers in Psychology, 2018)
The questions of whether episodic memory is a propositional attitude, and of whether it has propositional content, are central to discussions about how memory represents the world, what mental states should count as memories, and what kind of beings are capable of remembering. Despite its importance to such topics, these questions have not been addressed explicitly in the recent literature in philosophy of memory. In one of the very few pieces dealing with the topic, Jordi Fernández (2006) provides a positive answer to the initial questions by arguing that the propositional attitude view of memory, as I will call it, provides a simple account of how memory possesses truth-conditions. A similar suggestion is made by Alex Byrne (2010) when he proposes that perception and episodic memory have the same kind of content, differing only in degree. Against the propositional attitude view, I will argue that episodic memory does not have propositional content, and therefore, that it is not a propositional attitude. My project here is, therefore, mainly critical. I will show that, if empirical work is to inform our philosophical theories of memory in any way, we have good reasons to deny, or at least to be skeptical, of the prospects of the propositional attitude view of episodic memory.